Logical pluralism and linguistic relativism : a hypothesis about the relationship between logic, language and thought - Santos, Jorge Alejandro; Massolo, Alba; Durante, Santiago Gabriel (Universidade do Vale do Rio dos Sinos, 2024)
This paper aims to connect two debates about the relation among language, reasoning and thought that belong to different theoretical and disciplinary fields, but that are closely linked. On the one hand, the philosophical debate about logical pluralism. And, on the other hand, the linguistic debate around the Sapir-Whorf hypothesis. We propose a hypothesis compatible with a version of logical pluralism and linguistic relativism that makes it possible to explain the differences between thoughts expressed in different languages. This hypothesis, at the same time, supports the possibility of understanding and even translating different logical and linguistic variants. From a position akin to logical expressivism, we claim that there exists a proto-logic underlying all natural languages. The minimal logical operators proper of this proto-logic can be made explicit in a precise way in different formal systems. This gives rise to logical pluralism. We also offered an empirically informed philosophical argument in favor of this hypothesis.

Este artigo pretende conectar dois debates sobre a relação entre linguagem, raciocínio e pensamento que pertencem a campos teóricos e disciplinares diferentes, mas que estão intimamente ligados. Por um lado, o debate filosófico sobre o pluralismo lógico. E, por outro lado, o debate linguístico em torno da hipótese Sapir-Whorf. Propomos uma hipótese compatível com uma versão do pluralismo lógico e do relativismo linguístico que permite explicar as diferenças entre pensamentos expressos em diferentes línguas. Esta hipótese, ao mesmo tempo, sustenta a possibilidade de compreender e até traduzir diferentes variantes lógicas e linguísticas. De uma posição semelhante ao expressivismo lógico, afirmamos que existe uma protológica subjacente a todas as línguas naturais. Os operadores lógicos mínimos próprios desta protológica podem ser explicitados de forma precisa em diferentes sistemas formais. Isso dá origem ao pluralismo lógico. Também oferecemos um argumento filosófico empiricamente informado em favor desta hipótese.
Pluralismo lógico e relativismo linguistico: uma hipótese sobre a relação entre lógica, linguagem e pensamento
Keywords: Humanidades::Lenguas y Literatura